Low-end embedded Linux platform for network security application - Port scanning detector - Nasim, Ahmed; Zahereel Ishwar, Abdul Khalib; R., Badlishah Ahmad, Assoc. Prof. Dr.; Suhizaz, Sudin; Salina, Mohd Asi (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/